Community size and perception of older adults in the Cook Islands - Frackowiak, Tomasz (PLoS One, 2019)
Attitudes towards aging are often negative, a phenomenon known as ageism. However, personal contact with older adults and intergenerational exchange in the context of close families may mitigate such negative tendencies. So far, these effects have been studied in Western and industrialized contexts. The present study extended this work to the Cook Islands archipelago, a group of islands in the South Pacific characterized by low levels of industrialization and relative isolation from foreign influences. We tested the hypothesis that attitudes toward aging in the Cook Islands would be more positive than in the world at large, and that, within the archipelago, attitudes towards aging would be more positive in smaller, less industrialized communities with closer family ties. Participants (n = 70), were recruited from three islands varying in community size and strength of the family ties among inhabitants. They rated their aging attitudes on four dimensions. Contrary to our hypotheses, attitudes in the Cook Islands did not differ from those reported in industrialized nations and did not vary significantly across islands, even after controlling for personal contact to older adults. Potential limitations and implications for future research are discussed.